The relationship between food insecurity and risk of overweight or obesity in under 18 years individuals: A systematic review and meta-analysis - Ali Pourmotabbed; Seyedeh Parisa Moosavian; Amir Hadi; Hamed Mohammadi; Alireza Dadfarma; Shahabeddin Rezaei; Atefeh Babaei; Sajjad Moradi; Khadijah Mirzaei (International Journal of Preventive Medicine, 2020)
Objective: Food insecurit (FI) has been considered as reason for childhood and adolescent overweight/obesity (OW/OB). Hence, this study was undertaken to assess these relationships. Design: Related articles were found by searching the Web of Science, Scopus, PubMed and Embase databases until October 2019. Odds ratio (OR) was analized by a random-effects model. Standard methods were used for assessment of heterogeneity and publication bias. Data were available from 32 studies. The risk ratios of 139,762 participants were pooled from these articles for the meta-analysis. Results: This study domenstrated that children and adolescents in food-insecure condition are not at risk of OW/OB (OR = 1.02 95% CI: 0.99, 1.05). However, subgroup analysis indicated that FI related with inhanced risk of OW/OB in adolescents living in developed countries (OR = 1.14; 95% CI: 1.02, 1.27). Other subgroup analysis indicated that severe FI increased the risk of OW/OB among adolescents (OR = 1.24 95% CI: 1.03-1.49). In addition, we found that lower economic development significantly decreased risk of OW/OB among under 6 year children (OR = 0.88; 95% CI: 0.84, 0.93). Conclusions: Our results showed that higher FI degrees were related with more risks of OW/OB among adolescents (12–18 years). Moreover, the country economic levels had effect on the association between FI and risk of OW/OB.